Parental satisfaction with paediatric care with and without the support of an eHealth device: a quasi-experimental study in Sweden - Sarah Foldager Jeppesen; Rúnar Vilhjálmsson; Helene Åvik Persson; Inger Kristensson Hallström (BMC, 2024)
Abstract Background The period after a child is discharged from hospital is generally described as challenging for the parents. Their satisfaction with the health services received is an important indicator of the quality of care. eHealth devices are increasingly used in health care to support communication with parents. Differences in levels of parental satisfaction by modality of provided care or by parental background are largely unknown. This study aimed to describe satisfaction with health care between sociodemographic groups of parents, who either received or did not receive an eHealth device for communication between parents and hospital staff as a supplement to routine care after a child's discharge from neonatal or paediatric surgery departments. Methods Data from a quasi-experimental study was collected in the south of Sweden, between 2019 and 2021. The Pediatric Quality of Life Inventory™ (PedsQL) Healthcare Satisfaction Generic Module was used to assess the parents' satisfaction with different dimensions of health care. Seventy parents of children hospitalized in a neonatal or a paediatric surgery department were enrolled in intervention (eHealth device, n = 36) and control (no eHealth device, n = 34) groups. Results The parents reported high overall satisfaction with the health care provided and were also highly satisfied within different dimensions of care. Moreover, they reported high satisfaction with using an eHealth device, although having support from the eHealth device was related to neither higher nor lower levels of satisfaction with care. There was a significant difference between fathers and mothers in the multivariate sub-analysis in certain instances regarding satisfaction with communication and the level of inclusion. Conclusions Parents were very satisfied with the health care provided, whether or not they received eHealth. Further research looking at groups with and without the support of an eHealth device is required to further develop future paediatric and neonatal care interventions. Communication and support through eHealth can be a tool to alleviate the distress parents experience after their child's hospital admission, accommodate the family's transfer to home, and increase satisfaction with care, but it needs to be evaluated before being implemented. Trial registration Clinical Trials NCT04150120, first registration 4/11/2019.